Pengaruh Intellectual Capital, Dan Struktur Kepemilikan Terhadap Nilai Perusahaan (Studi Pada Perusahaan Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2009-2013) - Qomaria, Lailatul, Imronnudin, S.E, M.M, Ph.D (2016)
This study aimed to analyze the influence of intellectual capital dan ownership structure on firm value. Firm value reflected with stock price. The result of this study expected give an input and information that it takes the company as consideration in policy making in order to increase the company performance that can have a positive impact on firm value in the future. Data in this study obtained from publication of financial statement in Indonesian Capital Market Directory (ICMD) and www.idx.co.id. The research objects are Financial Sector Company which is listed on Indonesian Stock Exchange (IDX) period 2009 until 2013. The sampling method used purposive sampling with certain characteristic. The hypothesis analyze in this study used multiple regression linear. Result of this study showing that intellectual capital and ownership stucture silmutaneously had positive and significant influence on firm value. Intellectual capital had positif and significant influence on firm value partially. And managerial ownership and institusional ownership partially, had negative and not significance influence on firm value.